Peer-induced cocaine seeking in rats: comparison to nonsocial stimuli and role of paraventricular hypothalamic oxytocin neurons - Hammerslag, Lindsey R.; Humburg, Bree A.; Malone, Samantha G.; Beckmann, Joshua S.; Saatman, Kathryn E.; Grinevich, Valéry; Bardo, Michael T. (Addiction biology, 2022)
The purpose of this study was to determine if social vs nonsocial cues (peer vs light/tone) can serve as discriminative stimuli to reinstate cocaine seeking. In addition, to assess a potential mechanism, an oxytocin (OT) promoter-linked hM3Dq DREADD was infused into the paraventricular nucleus of the hypothalamus to determine whether peer-induced cocaine seeking is decreased by activation of OT neurons. Male rats underwent twice-daily self-administration sessions, once with cocaine in the presence of one peer (S+) and once with saline in the presence of a different peer (S−). Another experiment used similar procedures, except the discriminative stimuli were nonsocial (constant vs flashing light/tone), with one stimulus paired with cocaine (S+) and the other paired with saline (S−). A third experiment injected male and female rats with OTp-hM3Dq DREADD or control virus into PVN and tested them for peer-induced reinstatement of cocaine seeking following clozapine (0.1 mg/kg). Although acquisition of cocaine self-administration was similar in rats trained with either peer or light/tone discriminative stimuli, the latency to first response was reduced by the peer S+, but not by the light/tone S+. In addition, the effect of the conditioned stimulus was overshadowed by the peer S+ but not by the light/tone S+. Clozapine blocked the effect of the peer S+ in rats receiving the OTp-hM3Dq DREADD virus, but not in rats receiving the control virus. These results demonstrate that a social peer can serve as potent trigger for drug seeking and that OT in PVN modulates peer-induced reinstatement of cocaine seeking.